The Contextual Meaning of the Word Qadha (قضى) in the Qur’an: A Semantic Analysis - Tsaqalain, Tsiqah; Haeruddin, Haeruddin; Zuhriah, Zuhriah; Fitriani, Fitriani (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2026)
The lexeme qadha is one of the most frequent lexical items in the Qur’an, appearing 63 times in various morphological forms derived from the root q-d-y and exhibiting semantic variations across contexts. This study aims to identify its contextual meanings and examine how linguistic and situational contexts influence its interpretation in the Qur’anic text. This research employs a qualitative descriptive design using a contextual semantic approach. The data consist of all Qur’anic verses containing forms of qadha, analyzed using a semantic framework based on linguistic context (siyāq al-lughawī) and situational context (siyāq al-mawqif). The findings show that the basic meaning of qadha as a decree develops into several contextual meanings, including judgment, completion, creation, destruction, command, and death, depending on the context. These results confirm that lexical meaning is systematically shaped by context and highlight the broader relevance of contextual semantic analysis for linguistic and semantic studies of religious and classical texts